2018
DOI: 10.19106/jmedsci005002201805
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcomes in in vitro fertilization (IVF) pregnancies

Abstract: In vitro fertilization (IVF) has been associated with poor neonatal outcomes. Preterm birth, small-for-gestational age (SGA), and low birth weight (LBW) rates are approximately twice as high in IVF pregnancies than in natural pregnancies. The IVF procedures have become more routine in recent years in Indonesia, but there have been few assessments of neonatal outcomes. The study aimed to evaluate the risk of preterm birth, SGA, and LBW in IVF infants. This was a retrospective cohort study performed in Dr. Sardj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(31 reference statements)
1
1
0
1
Order By: Relevance
“…1,2 The number of neonates born through this process continues to increase, with an estimated 3-5 million IVF neonates worldwide since the first successful IVF and embryo transfer was reported in 1978. 3,4 In accordance with reports of success, IVF also poses potential risks for both mother and baby. 5 In most ARTs, higher numbers of embryos are transferred to the uterus, resulting in multiple pregnancies.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…1,2 The number of neonates born through this process continues to increase, with an estimated 3-5 million IVF neonates worldwide since the first successful IVF and embryo transfer was reported in 1978. 3,4 In accordance with reports of success, IVF also poses potential risks for both mother and baby. 5 In most ARTs, higher numbers of embryos are transferred to the uterus, resulting in multiple pregnancies.…”
supporting
confidence: 64%
“…In a comparison of natural conception and IVF, multiple pregnancies were higher in IVF. 4 Another study found that mothers who underwent ART conception had a 54 times higher chance of multiple pregnancies. 22 In order to reduce the incidence of multiple pregnancies while improving perinatal outcomes, many studies have focused on reduction of the number of embryos transferred into the uterus at one time.…”
Section: Discussionmentioning
confidence: 99%
“…Studi lain di Indonesia menunjukkan persentase kelahiran hidup sebesar 19,8% pada IVF. 4,5 their chances of becoming pregnant are reduced. The follicle-stimulating hormone (FSH Tujuan utama IVF adalah untuk mencapai potensi implantasi maksimum.…”
Section: Pendahuluanunclassified